A wolf called Romeo - Jans, Nick, 1955- (Houghton Mifflin Harcourt, 2014)
"No stranger to wildlife, Nick Jans had lived in Alaska for nearly thirty years. But when one evening at twilight a lone black wolf ambled into view not far from his doorstep, Nick would finally come to know this mystical species--up close as never before. [This book tells the] story of a wolf who returned again and again to interact with the people and dogs of Juneau, living on the edges of their community, engaging in an improbable, awe-inspiring interspecies dance and bringing the wild into sharp focus"--